Development of a sustainability index for South African dwellings incorporating green roofs, rainwater harvesting and greywater re-use - Van der Walt, Johannes Tinus (Stellenbosch : Stellenbosch University, 2012)
Thesis (MScEng)--Stellenbosch University, 2012.